"On-the-fly" coupled cluster path-integral molecular dynamics: impact of nuclear quantum effects on the protonated water dimer. Issue 22 (14th June 2015) - Spura, Thomas; Elgabarty, Hossam; Kühne, Thomas D.
<x xml:space="preserve">Abstract</x> "On-the-fly" coupled cluster-based path-integral molecular dynamics simulations predict that the effective potential of the protonated water–dimer has a single-well only.